A new species of Lonchophylla (Chiroptera, Phyllostomidae) from the Atlantic Forest of southeastern Brazil, with comments on L. bokermanni - Dias, Daniela; Esbérard, Carlos Eduardo L.; Moratelli, Ricardo (Zootaxa, 2013)
We examined Brazilian species of the nectar-feeding bats genus Lonchophylla (Phyllostomidae, Lonchophyllinae) to clarify the identity of Lonchophylla bokermanni and to determine the distribution of this and other species of Lonchophylla in eastern Brazil. As a result, we have found sufficient differences between Cerrado populations (including the type locality of L. bokermanni) and populations inhabiting the Atlantic Forest of southeastern Brazil,which warrant the treatment of the Atlantic Forest populations as a separate and new species. We describe this new species here as Lonchophylla peracchii, sp. nov. The new species appears to be restricted to the Atlantic Forest, whereas L. bokermanni is found only in Cerrado habitats.